Major Ocular Abnormalities Among Hemodialysis Patients in Indonesia - Sauli Ari Widjaja; Koichi Ono; Yoshimune Hiratsuka; Ima Yustiarini; Widodo Widodo; Akira Murakami (Acta Medica Indonesiana)
Background: This study aimed to identify the major ocular abnormality findings (i.e., cataract and conjunctival and corneal calcification (CCC)) among hemodialysis (HD) patients and their risk factors. Methods: A single institute-based cross-sectional study in Indonesia. Demographic data, medical histories, and complete ocular examinations were collected. For two major ocular abnormalities found, a generalized estimating equation was incorporated in a logistic regression model to assess the relationship with their risk factors. Results: We analyzed 318 eyes (159 individuals), of which 54.7% male and 45.3% female. The mean age was 51.6±11.3 years. The mean HD period was 3.5±3.2 years. Hypertension and diabetes mellitus (DM) was found in 81.1% and 34.6%, respectively. The major ocular abnormalities found were cataract (206 eyes; 64.78% (95% CI 59.53-70.03)), followed by CCC (135 eyes; 42.45% (95 % CI 37.02-47.88)). In a multivariate model, higher education (odds ratio (OR) 0.17; 95% CI 0.04-0.74), hypertension (OR 0.15; 95% CI 0.03-0.79), DM (OR 10.49; 95% CI 1.57-70.06), Systolic Blood Pressure (SBP) 120-129 mmHg (OR 0.05; 95% CI 0.003-0.69), SBP >140 mmHg (OR 0.05; 95% CI 0.004-0.67), Diastolic Blood Pressure (DBP) 80-89 mmHg (OR 7.44; 95% CI 1.13-48.73), and DBP >90 mmHg (OR 48.47; 95% CI 3.4-692.03) showed significant association with cataract. Meanwhile, there was no significant association between CCC and any predictor. Conclusion: Cataract and CCC were found to be the major ocular abnormalities among HD patients in this study, with DM and higher DBP as the risk factors for cataract. This finding supports recommendations for integrated regular eye screening in HD patients.